Pesan Komunikasi Interpersonal Orang Tua dan Anak Menurut Perspektif Alquran Surat Lukman ayat 12-19 - Riska Hayati; Muhtadiah Hasibuan; Lahmuddin Lahmuddin (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The purpose of this study is to answer how the interpersonal communication message of parents to their children contained in the Quran Surah Lukman verses 12-19. The problem described is the interpretation of Lukman's advice to his son and how good communication is established between them, because Lukman guides and advises his son with love and tenderness. Unlike the phenomenon that occurs today, not all parents have a good way of communicating like Lukman did with his son. In advising their children, some parents speak harshly and even hit their children. This type of research is Library Research, which is a study to collect data and information with the help of books, records, written historical stories and other library materials. This research uses a revelation approach using content analysis techniques. The data sources in this research are primary sources from the Quran and its translation, while the secondary sources are books and journals of previous research that support this research. The results of this study indicate that the message of interpersonal communication between parents and children from the perspective of the Qur'an Surah Lukman verses 12-19 is the prohibition of associating partners with Allah or committing shirk because it is a great sin and great injustice. Then the next message is the order to establish prayer, do good, especially to the mother and father and encourage the ma'ruf and prevent evil and be patient with what happens to someone, specifically in the context of the verse is patient in doing ma'ruf nahi mungkar, prohibition of being arrogant or haughty, simple in walking and softening the voice in speaking.